THE INFLUENCE MSMEs AND CREATIVE ECONOMY ON ECONOMIC RESILIENCE IN THE NEW NORMAL (CASE STUDY: UNSRAT STUDENT) - Ngantung, Edward M. C.; Tulung, Joy E.; Arie, Fitty Valdi (Universitas Sam Ratulangi, 2021)
MSMEs are one of the sectors hardest hit from the Covid-19 pandemic. Whereas the sector is the sector that absorbs the most labor around 97%, digital technology that is applied in this economic sector, will encourage opportunities for the growth of MSMEs that drive the economy. This study aims to analyze the Influence of MSMEs and Creative Economies on Economic resilience in the new normal. The population in this study were students of Sam Ratulangi University. The sampling technique was purposive sampling and obtained 55 businesses that were used as samples. The multiple regression analysis methods is used to analyze the effect of the independent variable on the dependent variable. The results showed that partially MSMEs did not affect economic resilience in the new normal and Creative Economies had a significant positive effect on economic resilience in the new normal. Simultaneously, MSMEs and Creative Economies have a significant effect on Economic resilience in the new normal. MSMEs are encouraged to always improve their innovation so that they continue to provide the latest breakthroughs and always survive in any situation.Â Keywords: MSMEs, Creative Economy, Economic Resilience